EMPOWERING POULTRY FARMERS THROUGH TRAINING ON PREPARING FEED RATIONS BASED ON LOCAL RAW MATERIALS IN MOJOKERTO REGENCY - Azizah, Siti; Aprylasari, Dede; H. Djunaidi, Irfan; Rachmawati, Achadiah; Indrati, Rositawati (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
The poultry industry in Indonesia, especially in Mojokerto Regency, plays a vital role in providing animal protein. This district has great potential with a significant poultry population, including free-range chickens, laying hens, broilers, and muscovy ducks. One of the main challenges faced is feed management, which accounts for 60-70% of total production costs. Rising industrial feed prices and fluctuating dependence on imported feed demand innovative solutions in feed management. This research aims to maximize the use of raw local feed materials and increase poultry farmers' competence in preparing rations in the Mojokerto Regency. This research uses a level III action research design, which includes interviews, observation, and documentation. The sample consisted of 20 breeders selected by purposive sampling. The extension program was developed to increase farmers' knowledge and skills in preparing feed using local ingredients. Program evaluation showed a significant increase in knowledge about feed (33.47%), rearing management (29.13%), and animal health (30.22%). The research showed that this training increased farmers' understanding of local feed management, effective rearing management, and livestock health. Applying local feed ingredients can reduce dependence on imported feed, reduce production costs, and support local food security. Apart from that, this training also positively impacts livestock welfare and the local economy. With an effective extension program, it is hoped that farmers in Mojokerto can increase the independence and sustainability of their livestock businesses. Keywords: Poultry Farming, Local Feed, Extension, Mojokerto Regency, Feed Management